1994
DOI: 10.1172/jci117184
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytosis and natural killer cell function parallel neurobehavioral fatigue induced by 64 hours of sleep deprivation.

Abstract: The hypothesis that sleep deprivation depresses immune function was tested in 20 adults, selected on the basis of their normal blood chemistry, monitored in a laboratory for 7 d, and kept awake for 64 h. At 2200 h each day measurements were taken of total leukocytes (WBC), monocytes, granulocytes, lymphocytes, eosinophils, erythrocytes (RBC), B and T lymphocyte subsets, activated T cells, and natural killer (NK) subpopulations (CD56/CD8 dual-positive cells, CD16-positive cells, CD57-positive cells). Functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
230
2
8

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(257 citation statements)
references
References 37 publications
15
230
2
8
Order By: Relevance
“…Previous studies have reported a relationship between sleep deprivation and increased leukocytosis (Born et al, 1997;Dinges et al, 1994), which was replicated in this study. The increased neutrophilia observed in this study the morning after sleep deprivation (Fig.…”
Section: Il-8 Productionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previous studies have reported a relationship between sleep deprivation and increased leukocytosis (Born et al, 1997;Dinges et al, 1994), which was replicated in this study. The increased neutrophilia observed in this study the morning after sleep deprivation (Fig.…”
Section: Il-8 Productionsupporting
confidence: 85%
“…(Born et al, 1997;Dinges et al, 1994). It appears that one night's sleep deprivation elevated the platelet count on subsequent days in the Placebo…”
Section: Correlations Among Subjective Ratingsmentioning
confidence: 99%
“…The effects of sleep on human immune functions (compared with continuous wakefulness) are controversial. Some studies showed that sleep is associated with a reduction in the numbers of immune cell types (16,51), including monocytes and T lymphocytes, whereas other studies reported an enhancement or no change (51)(52)(53). The situation is more complex for cytokines, with some affected (increase and decrease) and others unchanged, with discrepancies observed among studies (38).…”
Section: Discussionmentioning
confidence: 99%
“…There are several laboratory studies that have used simulated night work to investigate the effects of partial or total sleep deprivation on immune function [6][7][8][9][10][11] . Both enhancing and suppressive effects on NK cell activity and lymphocyte subsets have been reported.…”
mentioning
confidence: 99%